Neuropathology and virus in brain of SARS-CoV-2 infected non-human primates - Rutkai, Ibolya; Mayer, Meredith G.; Hellmers, Linh M.; Ning, Bo; Huang, Zhen; Monjure, Christopher J.; Coyne, Carol; Silvestri, Rachel; Golden, Nadia; Hensley, Krystle; Chandler, Kristin; Lehmicke, Gabrielle; et al. (Nature communications, 2022)
Neurological manifestations are a significant complication of coronavirus disease (COVID-19), but underlying mechanisms aren’t well understood. The development of animal models that recapitulate the neuropathological findings of autopsied brain tissue from patients who died from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection are critical for elucidating the neuropathogenesis of infection and disease. Here, we show neuroinflammation, microhemorrhages, brain hypoxia, and neuropathology that is consistent with hypoxic-ischemic injury in SARS-CoV-2 infected non-human primates (NHPs), including evidence of neuron degeneration and apoptosis. Importantly, this is seen among infected animals that do not develop severe respiratory disease, which may provide insight into neurological symptoms associated with “long COVID”. Sparse virus is detected in brain endothelial cells but does not associate with the severity of central nervous system (CNS) injury. We anticipate our findings will advance our current understanding of the neuropathogenesis of SARS-CoV-2 infection and demonstrate SARS-CoV-2 infected NHPs are a highly relevant animal model for investigating COVID-19 neuropathogenesis among human subjects. COVID-19 can result in neurological manifestations and animal models could provide insights into the mechanisms. Here, the authors describe neuroinflammation, microhemorrhages and brain hypoxia in SARS-CoV-2 infected non-human primates, including in animals that don’t develop severe respiratory disease.